PENGARUH MEDIA PAMERAN BUDAYA UNTUK MENUMBUHKAN PENGETAHUAN SISWA TENTANG WARISAN BUDAYA SUMATERA SELATAN PADA SISWA KELAS IV SD NEGERI 232 PALEMBANG - Andini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the extent to which the use of cultural exhibition media influences students' knowledge of South Sumatra's cultural heritage. The study was conducted on fourth-grade students at SD Negeri 232 Palembang, using a quantitative approach with a quasi-experimental method and a non-equivalent control group design. The subjects of the study consisted of two classes: an experimental class that received learning treatment using cultural exhibition media, and a control class that used digital media. The research instrument was a knowledge test in the form of a pretest and posttest. The results of the analysis showed that there was a significant change in the experimental class, with an average pretest score of 44.00 which became 93.80 in the posttest. In contrast, the control class experienced a change from 46.36 to 69.31. These findings indicate that cultural exhibition media can be an effective alternative learning media in fostering students' understanding of local cultural richness. The implications of this study encourage the use of media based on direct experience in local content learning in elementary schools.